A priori estimates for solutions of the first initial boundary-value problem for systems of fully nonlinear partial differential equations - Belopol’skaya, Ya. I. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We prove a priori estimates for a solution of the first initial boundary-value problem for a system of fully nonlinear partial differential equations (PDE) in a bounded domain. In the proof, we reduce the initial boundary-value problem to a problem on a manifold without boundary and then reduce the resulting system on the manifold to a scalar equation on the total space of the corresponding bundle over the manifold.